A novel autonomous remote system applied in agriculture using transmission control protocol - Anass Deroussi; Abdessalam Ait Madi; Imam Alihamidi; Lalla Amina Charaf; Mohammed Saber; Anass Erraoui; Adnane Addaim (International Journal of Reconfigurable and Embedded Systems (IJRES), 2022)
An internet of things (IoT) irrigation system is challenged by several issues, such as cost, energy consumption, and data storage. This paper proposes a novel energy-efficient, cost-effective IoT system called "NewAgriCom" to monitor agricultural field water flow. NewAgriCom works with an embedded energy harvesting system, is an autonomous remote supervisory control and data acquisition (SCADA) based on a general packet radio service (GPRS) cellular network that effectively communicates irrigation field data to the Node.js server using SIM808 EVBV3.2 modem. In javascript object notation (JSON) format, data is transmitted over the hypertext transfer protocol (HTTP) protocol to the MySQL database. Then data are transferred to the proposed IoT platform, which gives us a hand to control actuators, visualise, store and download the data. NewAgriCom can significantly reduce water consumption. It can set a schedule to control water automatically at specific times in various modes, including normal, light, and deep sleep modes. It regularly provides the location, time, signal strength, and the state of actuators with the identifier of every device remotely on the IoT Platform.